2010
DOI: 10.1186/1742-6405-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of highly active antiretroviral therapy in the context of universal access to healthcare: the U.S. Military HIV Natural History Study

Abstract: BackgroundTo examine the outcomes of highly-active antiretroviral therapy (HAART) for individuals with free access to healthcare, we evaluated 2327 patients in a cohort study composed of military personnel and beneficiaries with HIV infection who initiated HAART from 1996 to the end of 2007.MethodsOutcomes analyzed were virologic suppression (VS) and failure (VF), CD4 count changes, AIDS and death. VF was defined as never suppressing or having at least one rebound event. Multivariate (MV) analyses stratified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 55 publications
5
85
0
Order By: Relevance
“…22 In one study, 21 virological failure combined with viral resistance occurred in 24.1% of patients with interruption and resumption of treatment using stavudine (d4T) + 3TC + NVP, d4T + 3TC + EFZ and AZT + 3TC + NVP regimens. Other studies showed that d4T regimens had virological failure in 16.9%, motivated by predictors such as treatment interruptions, use of NVP, initial LTCD 4 < 25 cells/dL, initial VL ≥ 400 copies/mL, and stage of AIDS, 14,16,17,19,20 while only 7.7 and 2.65% obtained treatment failure with the same regimens in other studies. 18,25 These differences may be justified by factors such as ARV classes (NRTI, NNRTI and PI), adherence, toxicity, adverse reactions, incorrect drug combinations in coinfections, and pharmacogenetics of patients.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…22 In one study, 21 virological failure combined with viral resistance occurred in 24.1% of patients with interruption and resumption of treatment using stavudine (d4T) + 3TC + NVP, d4T + 3TC + EFZ and AZT + 3TC + NVP regimens. Other studies showed that d4T regimens had virological failure in 16.9%, motivated by predictors such as treatment interruptions, use of NVP, initial LTCD 4 < 25 cells/dL, initial VL ≥ 400 copies/mL, and stage of AIDS, 14,16,17,19,20 while only 7.7 and 2.65% obtained treatment failure with the same regimens in other studies. 18,25 These differences may be justified by factors such as ARV classes (NRTI, NNRTI and PI), adherence, toxicity, adverse reactions, incorrect drug combinations in coinfections, and pharmacogenetics of patients.…”
Section: Resultsmentioning
confidence: 93%
“…14,15,17,[25][26][27] Other studies also reveal that changes in HAART after six months may also occur after confirmation of immuno-virological failure and low adherence. 16,17,[19][20][21] In our population, therapeutic failure, although not the most prevalent cause for HAART replacement, was the reason for switching drugs in 12.6% of the cases that used initial TDF + 3TC + EFZ and AZT + 3TC + EFZ regimens. Other authors showed that TDF + 3TC + EFZ schemes resulted in viral suppression in 92% of patients and virological failure in 8 and 10.8% of patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research and development in HIV-1/AIDS therapy has been focusing on interrupting many steps in HIV-1 life cycle, and the use of current combination antiretroviral therapy (cART) has been relatively successful with respect to controlling the plasma viral load level to below the limits of current assay detection capabilities (Doherty, Ford, Vitoria, Weiler, & Hirnschall, 2013;Gulick et al, 1997;Hammerle, Himmelspach, Dorner, & Falkner, 1997;Hirnschall, Harries, Easterbrook, Doherty, & Ball, 2013;Marconi et al, 2010;Williams, Lima, & Gouws, 2011). One of the cART regiments has included an entry inhibitor, with the inclusion of one of the two current U.S. Food and Drug (FDA)-approved entry inhibitors used in humans either Enfuvirtide or Maraviroc (LaBonte, Lebbos, & Kirkpatrick, 2003;Lieberman-Blum, Fung, & Bandres, 2008;MacArthur & Novak, 2008).…”
Section: Summary Of Viral Entry Coreceptor Utilization Viral Exit mentioning
confidence: 99%